Tunable open circuit voltage by engineering inorganic cesium lead bromide/iodide perovskite solar cells - Ng, Chi Huey; Ripolles, Teresa S.; Hamada, Kengo; Teo, Siow Hwa; Lim, Hong Ngee; Bisquert, Juan; Hayase, Shuzi (Nature Research, 2018)
Perovskite solar cells based on series of inorganic cesium lead bromide and iodide mixture, CsPbBr3-xI x , where x varies between 0, 0.1, 0.2, and 0.3 molar ratio were synthesized by two step-sequential deposition at ambient condition to design the variations of wide band gap light absorbers. A device with high overall photoconversion efficiency of 3.98 % was obtained when small amount of iodide (CsPbBr2.9I0.1) was used as the perovskite and spiro-OMeTAD as the hole transport material (HTM). We investigated the origin of variation in open circuit voltage, Voc which was shown to be mainly dependent on two factors, which are the band gap of the perovskite and the work function of the HTM. An increment in Voc was observed for the device with larger perovskite band gap, while keeping the electron and hole extraction contacts the same. Besides, the usage of bilayer P3HT/MoO3 with deeper HOMO level as HTM instead of spiro-OMeTAD, thus increased the Voc from 1.16 V to 1.3 V for CsPbBr3 solar cell, although the photocurrent is lowered due to charge extraction issues. The stability studies confirmed that the addition of small amount of iodide into the CsPbBr3 is necessarily to stabilize the cell performance over time.